A mixed methods investigation into adolescents’ use of mental health apps - Pascoe, Hannah (2021)
The prevalence of mental health needs in children and young people continues to outweigh the availability of support and services (Ford et al., 2007; Vizard et al., 2020). Alongside these systemic barriers, adolescents are identified as a population that may experience personal barriers to seeking mental health support (Radez et al., 2020). With advances in and increased use of technology, research in recent years has explored how technology can be used to support mental health and wellbeing, particularly amongst adolescents and young people (Donker et al., 2013; Hollis et al., 2017). The current study sought to explore older adolescents’ use of mental health apps (MHApps) in a real-life context, to increase awareness of how this population are engaging with MHApps and to give direction to future research. An online survey was conducted within sixth form provisions in the East Midlands, with pupils aged 16-to-18 years. Quantitative data gave insight into adolescents’ use of MHApps and was triangulated with qualitative data through a content analysis of most-used MHApp features by app function.